2022
DOI: 10.1053/j.jvca.2021.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Post-Acute COVID-19 Syndrome for Anesthesiologists: A Narrative Review and a Pragmatic Approach to Clinical Care

Abstract: Post-acute coronavirus disease 2019 (COVID-19) syndrome is a novel, poorly understood clinical entity with life-impacting ramifications. Patients with this syndrome, also known as “ COVID-19 long-haulers ,” often present with non-specific ailments involving more than one body system. The most common complaints include dyspnea, fatigue, brain fog, and chest pain. There is currently no single agreed-upon definition for post-acute COVID-19 syndrome, but most agree that criterion for this sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 161 publications
0
7
0
1
Order By: Relevance
“…A study by Frankfurt University Hospital revealed that 78% of survivors of COVID-19 had CV alterations, and 60% of them still showed signs of persistent myocardial inflammation more than two months after the diagnosis [74]. The results propose that long-term sequelae, for example, arrhythmias and HF, are also probable in apparently healthy people [75].…”
Section: Cardiovascular Involvementmentioning
confidence: 97%
“…A study by Frankfurt University Hospital revealed that 78% of survivors of COVID-19 had CV alterations, and 60% of them still showed signs of persistent myocardial inflammation more than two months after the diagnosis [74]. The results propose that long-term sequelae, for example, arrhythmias and HF, are also probable in apparently healthy people [75].…”
Section: Cardiovascular Involvementmentioning
confidence: 97%
“…The emerging knowledge regarding the manifestations and pathophysiology of Long COVID informs the perioperative space, raising concern for postural orthostatic tachycardia syndrome (POTS), orthostasis, post-exertional malaise (PEM), other cardiopulmonary complications, and neuropsychiatric manifestations. 44 …”
Section: Mechanism Of Perioperative Risk and Areas Of Uncertaintymentioning
confidence: 99%
“…Published literature related to pain after SARS‐CoV‐2 infection includes survivors with variable severity of illness and a heterogeneous spectrum of symptoms. Hence, pain consequences are described in different terms, such as post‐acute coronavirus disease 2019/COVID‐19 syndrome, COVID‐19 long‐haulers, post‐acute sequelae of SARS‐CoV‐2 infection and long COVID [ 6 , 12 ]. Some consider the constellation of symptoms similar to ‘post‐intensive care syndrome’ [ 9 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…A preliminary literature search identified a need to report the consequences of the pandemic for chronic pain to help improve understanding and serve the needs of affected populations, both for clinical care and research endeavours. Published reviews or editorials have focused on a combination of post‐COVID‐19 symptoms [ 6 ]; considered only acute pain presentation from the infection [ 7 , 8 ]; highlighted the potential for the increased rate and the need for rehabilitation [ 9 , 10 ] or have become outdated [ 11 ]. Considering this gap, we set to review the published reports to evaluate the burden, type and progression of new‐onset chronic pain after SARS‐CoV‐2 infection, as well as the influence of the pandemic on chronic pain patients.…”
Section: Introductionmentioning
confidence: 99%